Sports Aggression and Basketball Performance of Filipino Employees towards Social Skills Enhancement - Samala, Hazel; P. Samala, Jan Eliezer Michael (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to determine the perceptions of the 140 male employees in a State University in Cavite, Philippines on sports aggression and its relationship to their level of performance in basketball. A descriptive research design was used through survey questionnaires on the perceptions of the respondents on sports aggression and their level of performance in basketball. The data were obtained using both primary and secondary sources through observation and survey method. The statistical tools used to analyze the data were frequency and percentage, composite mean, standard deviation, t-test, Analysis of variance (ANOVA), and Pearson product moment correlation (Pearson r). Results of this research study shows that the male employees are dominated by young people with age 21 to 30. More than half of the respondents are faculty members of the State University. Among the four (4) factors of sports aggression, physical aggression, anger and hostility were found significant of the respondents when grouped according to age, while verbal aggression was found not significant. As for the nature of employment, the respondents’ perceptions on sports aggression was found not significant. When the differences between the respondents’ perceptions on sports aggression and their performance in basketball was tested, it resulted to a significant relationship. The level of performance in playing basketball resulted to below average performance after the conduct of this study. The researchers recommend for an employee basketball clinic that will help them develop their basketball skills since they are teaching the sport to their students as part of their curriculum. Since there is significant difference between the respondents’ perceptions on sport aggression and their performance in basketball, the researchers recommend for further studies to help understand how sports aggression affect the performance in playing basketball.